Наповнені пористі композити на основі кополімерів полівінілпіролідону - Дзяман, Ірина Зіновіївна (Національний університет "Львівська політехніка", 2016)
Дисертаційна робота присвячена розробленню основ технології одержання наповнених мінеральними наповнювачами пористих срібловмісних композиційних матеріалів медичного призначення на основі кополімерів полівінілпіролідону з метакриловими естерами. Досліджено закономірності полімеризації композицій метакрилових естерів з полівінілпіролідоном у присутності мінеральних наповнювачів гідроксіапатиту, воластоніту та монтморилоніту. Встановлено вплив природи і кількості мінерального наповнювача, метакрилового мономера та солей аргентуму на закономірності одержання, структуру та властивості композитів. Розроблено основи формування пористої структури срібловмісних композитів, обґрунтовано оптимальний склад полімер-мономерної композиції, природу та кількість наповнювача, пороутворювача та стабілізатора піни. Досліджено закономірності одержання наночастинок срібла з його солей у присутності полівінілпіролідону під час формування композиту. Розроблено принципову технологічну схему та технологічні режими одержання пористих композитів. Розроблено тимчасовий технологічний регламент, одержано експериментальні зразки композитів і досліджено їхні властивості. Диссертация посвящена разработке основ технологии получения наполненных минеральными наполнителями пористых серебросодержащих композиционных материалов медицинского назначения на основе сополимеров поливинилпирролидона с метакриловыми эфирами. Исследованы закономерности полимеризации композиций метакрилових эфиров с поливинилпирролидоном в присутствии минеральных наполнителей гидроксиаппатита, волластонита и монтмориллонита. Установлено влияние природы и количества минерального наполнителя, метакрилового мономера и солей серебра на закономерности получения, структуру и свойства композитов. Разработаны основы формирования пористой структуры серебросодержащих композитов, обоснован оптимальный состав полимер-мономерных композиций, природа и количество наполнителя, порообразователя и стабилизатора пены. Исследованы закономерности получения наночастиц серебра из его солей в присутствии поливинилпирролидона при формировании композита. Разработана принципиальная технологическая схема и технологические режимы получения пористых композитов. Разработан временный технологический регламент, получены экспериментальные образцы композитов и исследованы их свойства. The thesis is devoted to development of technology bases for obtaining of the filled with mineral fillers porous silver-containing composite materials of medical purpose based on polyvinylpyrrolidone and methacrylic esters copolymers. The polymerization regularities for compositions of polyvinylpyrrolidone and methacrylic esters in the presence of mineral fillers such as hydroxyapatite, wollastonite and montmorillonite have been investigated. A polymerization reaction, which, depending on conditions, may occur by radical or ionic mechanisms has been presented. It is determined, that the ultrasound applying leads to significantly accelerate the polymerization, which is accompanied by a simultaneous foaming of the compositions. The above mentioned has been applied during the development of technology basis for porous composites obtaining. It was researched the composition of copolymers which were obtained by composition’s copolymerization of the glycols (met) acrylic esters with polyvinylpyrrolidone in the presence of fine mineral fillers. The influence of nature, amount of filler and monomer-polymer composition on effectiveness and grafting degree has been determined and used for directed regulation of copolymers composition. The regularities of silver nanoparticles formation from respective salts including the ones during composites congelation have been defined. The bases of porous structure of silver-containing composites forming with mineral filler have been developed. The technology is based on the use of organic easy-boiling pore-formers and high-molecular weight foam stabilizers. The optimal composition, temperature and timing for obtaining of the composites has been determined. Montmorillonite-containing compositions have the highest reactivity. The influence of the nature, amount of mineral filler and argentums salts on the structure, physical, mechanical and antibacterial properties of developed composites has been studied. Salts of silver reduce the rate of polymerization, especially at the initial stages of the reaction, exhibiting inhibitory action. The technological scheme and modes of porous composites obtaining have been developed. The temporary production schedules were developed, experimental models of the composites were obtained and their properties were studied. Biomedical testing found that developed osteoplastic composites show fungi- and bactericidal properties, in particular regarding Escherichia coli, Staphylococcus aureus and A. Niger, providing their efficiency during exploitation.
Наполненные пористые композиты на основе сополимеров поливинилпирролидона
Filled porous composites based on polyvinylpyrrolidone copolymers
Keywords: полівінілпіролідон; 2-гідроксіетилметакрилат; мінеральний наповнювач; гідроксіапатит; монтморилоніт; воластоніт; пористий композит; поливинилпирролидон; 2-оксиэтилметакрилат; минеральный наполнитель; гидроксиаппатит; монтмориллонит; волластонит; пористый композит; polyvinylpirrolidonе; 2-hydroxyethylmethacrylate; mineral filler; hydroxyapatite; wollastonite; montmorillonite; porous composite